The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1993
DOI: 10.1038/hdy.1993.23
|View full text |Cite
|
Sign up to set email alerts
|

A general model for the genetic control of copper tolerance in Silene vulgaris: evidence from crosses between plants from different tolerant populations

Abstract: Copper tolerance in Silene vulgaris seems to be controlled by two major genes. One segregates only in crosses to non-tolerants but never in crosses between tolerants originating from different isolated populations. The second segregates only in crosses to plants from the most tolerant population. The level of tolerance in tolerant plants seems to be controlled by two additional genes, which are hypostatic to the first major gene. They segregate in crosses to non-tolerants but not in crosses between equally hom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0
1

Year Published

1995
1995
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(44 citation statements)
references
References 6 publications
4
39
0
1
Order By: Relevance
“…exposure to very high level of metals in soils) (Meerts & Van Isacker, 1997). Genetic variation in the degree of tolerance in species showing ecotypic tolerance is well documented (Macnair et al, 1992 ;Schat & Ten Bookum, 1992 ;Schat et al, 1993Schat et al, , 1996Smith & Macnair, 1998). Smith & Macnair (1998) have shown that in Cu-tolerant Mimulus guttatus the variation in Cu tolerance observed among the tolerant populations was due to a variation in modifier genes and not to the major tolerance gene itself.…”
Section: Degree Of Tolerance In Arabidopsis Halleri Populationsmentioning
confidence: 99%
See 1 more Smart Citation
“…exposure to very high level of metals in soils) (Meerts & Van Isacker, 1997). Genetic variation in the degree of tolerance in species showing ecotypic tolerance is well documented (Macnair et al, 1992 ;Schat & Ten Bookum, 1992 ;Schat et al, 1993Schat et al, , 1996Smith & Macnair, 1998). Smith & Macnair (1998) have shown that in Cu-tolerant Mimulus guttatus the variation in Cu tolerance observed among the tolerant populations was due to a variation in modifier genes and not to the major tolerance gene itself.…”
Section: Degree Of Tolerance In Arabidopsis Halleri Populationsmentioning
confidence: 99%
“…Because all populations of A. halleri are tolerant, it means that the genes for tolerance per se are fixed in the species, and variation in tolerance between populations must be caused by variation in modifier genes (Schat et al, 1993 ;Smith & Macnair, 1998). Populations from uncontaminated sites were slightly less Zn tolerant than those from contaminated sites.…”
Section: Origin and Evolution Of Constitutive Tolerance And Hyperaccumentioning
confidence: 99%
“…Tolerance to a range of metals has evolved in many species exposed to elevated soil metal concentrations. For a number of metals, including zinc, copper and arsenic, genetic analysis has shown that this characteristic is controlled by a small number (one or two) of major genes, with additional modi¢ers determining the level of tolerance displayed (Schat et al 1993;Smith & Macnair 1998). The relationship between tolerance and hyperaccumulation is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Whether any of these genes is allelic to the single major gene conferring leaf dissection in the Oland population is still uncertain, but it seems safe to conclude that different genetic mechanisms are responsible for the finely divided leaves of these populations. Other cases in which the genetic basis of the same adaptation differs between species or conspecific populations of plants include floral morphology (Prazmo, 1965;Mayer & Charlesworth, 1992;Fenster & Barrett, 1994), heavy metal tolerance (Macnair, 1976;Schat et a!., 1993) and herbicide resistance (Miller et al, 1973).…”
Section: Discussionmentioning
confidence: 99%